Materials for Biofuels. - Ragauskas, Arthur J. (Materials and Energy., 2014)
This invaluable book provides a broad and detailed introduction to the fascinating and hot research subject of transformation of biomass-related materials to biofuels. Biofuel production can be categorized into a variety of novel conversion and refinery development technologies. However, biomass recalcitrance is the biggest challenge blocking the way in biofuel conversion. This book provides an enlightening view of the frontiers in leading pretreatments, downstream enzymatic hydrolysis, fermentation technology, corrosion issues in biofuel and merging biofuels technology into a pulp mill to pav.